Efektivitas Pengelolaan Dana Bantuan Operasional Sekolah Terhadap Peningkatan Mutu Pendidikan Di Sma Negeri 3 Polewali - Muwahid, Fadli; Azis, Muhammad; Azis, Fajriani (STIE AMKOP, 2024)
The Effectiveness of School Operational Assistance Fund Management on the Improvement of Education Quality at SMA Negeri 3 Polewali. Bachelor's Thesis in Accounting Education Program. Faculty of Economics and Business. State University of Makassar. Supervisors: Prof. Dr. H. Muhammad Azis, M.Si, and Fajriani Azis, S.Pd., S.E., M.Si. This study aims to analyze the effectiveness of school operational assistance fund management on the improvement of education quality at SMA Negeri 3 Polewali and to analyze the inhibiting factors affecting the effectiveness of school operational assistance fund management at SMA Negeri 3 Polewali in enhancing education quality. This research uses qualitative research to describe the situation and conditions of the research object based on written and oral data obtained. The informants interviewed consisted of 7 individuals, including the school principal, school treasurer, school staff, and SMA Negeri 3 Polewali students. Data validation techniques used member check. Data analysis techniques used data condensation, data presentation, and drawing conclusions. The research findings indicated that: 1) The effectiveness of School Operational Assistance Fund Management significantly influenced the improvement of education quality at SMA Negeri 3 Polewali based on the school's activity plans and budget. The analysis of student achievements and the progress of educators' competencies supported the positive impact on education quality. Specifically, student achievements in various competitions reflected the success of programs funded by the School Operational Assistance Fund. The accountability reports for fund allocation also followed proper procedures according to provincial regulations through the School Operational Assistance Fund portal. 2) Factors hindering the effectiveness of fund management at SMA Negeri 3 Polewali in improving education quality included delays in fund disbursement, late submission of accountability reports by activity organizers utilizing the funds, and slow compilation of accountability reports received by the school treasurer for submission to the government through the School Operational Assistance Fund portal. Keywords: Effectiveness, school operational assistance fund management, quality